Di-n-butylbis(N-cyclohexyl-N-ethyldithiocarbamato-kappa 2 S,S')tin(IV) - Awang, N.; Baba, I.; Yamin, B.M.; Ng, S.W. (International Union of Crystallography, 2010)
The SnIV atom in the title compound, [Sn(C(4)H(9))(2)(C(9)H(16)NS(2))(2)], is chelated by the two dithiocarbamate ions in a six-coordinate skew-trapezoidal-bipyramidal geometry. The two butyl groups are disordered over two positions in a 1:1 ratio.